Spatialised ecosystem modelling to evaluate the influences of marine protected areas and provisioning ecotourism on the foraging and distributional response of top predators from Mossel Bay to Algoa Bay, South Africa - Grusd, Samantha Paige (Department of Biological Sciences, 2025)
High trophic level ecosystem-regulating top predators are an important facet in the structure and functioning of the South-East coast of South Africa. This region is influenced by the warm, fast-flowing Agulhas Current, which make it a highly productive biodiversity hotspot. This consequently provides ideal conditions for commercial fishing, spatial management, and shark cage diving ecotourism that involves provisioning (attracting sharks to tourists); all of which have unknown implications regarding the behavioural and foraging response of top predators in the system. The Ecopath with Ecosim (EwE) and Ecospace modelling framework was utilised to investigate the distributional response of sharks and top predators on the South-East coast to the introduction of two new MPAs (in 2019) and seasonal provisioning for shark cage diving (in 2020), over a 35-year simulation period. A mass-balance Ecopath model was designed and parameterised for the 2008–2018 data period as a foundation for the spatial Ecospace models. A baseline Ecospace model was constructed, calibrated and validated against field observations to act as a reference scenario for the two exploratory models– these were i) the MPA model, which was built directly onto the baseline model and introduced the Addo Elephant National Park and Port Elizabeth (PE) Corals MPAs into the model in August 2019; and ii) the provisioning model, which built onto the MPA model, as the new shark cage diving operation in Algoa Bay occurs within the bounds of the Addo MPA. Spatial indicators (e.g., Biomass (B)mpa/Bbase, Bprovisioning/Bmpa) were calculated at various model timesteps to analyse the potential shift in top predator concentration over time and quantify their distributional response five, 15 and 25 years following the implementation of new MPAs and provisioning operation. There was a consistent distributional shift of shark and top predator concentration in response to the new MPAs and provisioning operation. Top sharks with inshore South-East coast nursery areas (smooth hammerhead, dusky, raggedtooth) and less-transient top predators (humpback dolphin, sevengill shark) evidently received positive indirect benefits of the coastal MPAs, particularly Addo (e.g., sufficient prey availability and remaining in the area for longer periods) throughout the simulation, compared to the transient top predators. This subsequently influenced the potential availability of these coastal predators for consumption by great white sharks in Algoa Bay, once seasonal provisioning was concurrently introduced to the model and white sharks became more concentrated around the Algoa Bay provisioning site. However, changes in total system biomass were minimal, and there was no indication of adverse cascading effects at the ecosystem level under current model parameterisations. Assessing the response of top predators to changes in a system is important for understanding the system's underlying dynamics, particularly in a world where the ecotourism and fishing industries are rapidly growing, and future resource management may be necessary. While previous studies have assessed various ecosystem responses to MPAs using Ecospace, this was the first study to model the ecotourism activity of shark cage diving spatially, and presents a novel approach to modelling the potential trophic effects of introducing anthropogenic activities into the marine environment.